Implementation of Character Education in PAI Subjects in the Independent Curriculum - Suhermanto; Mansyuri, Arif; Ma`arif, Muhammad Anas; Sebgag, Saliha (Program Studi Pendidikan Agama Islam (PAI), 2024)
The world of education is experiencing a character crisis in students due to the COVID-19 pandemic, when face-to-face learning is implemented, several cases such as conflict, violence, juvenile delinquency, sexual harassment, and bullying begin to appear in the school and community environment. This is almost felt in all schools, including SMA Al Azhar Menganti Gresik. This study aims to describe the implementation and implications of character education in PAI subjects in the independent curriculum which refers to dimension 1 P5 at Al Azhar Menganti Gresik High School. This type of research uses descriptive qualitative with a case study approach. Data were obtained through observation, interview, and documentation techniques. Data analysis techniques through data collection, reduction, presentation, and verification of data. The results showed that the implementation of character education in PAI subjects was good. The integration of teaching tools with P5 dimensions, especially dimension 1, can improve character-building in students. School culture also supports the improvement of character building in students. Supporting factors include the concern of the principal, MGMPS PAI, subject teachers, infrastructure, school, and extracurricular programs. The inhibiting factor in the formation of student's character is the limited communication between teachers, cottage caregivers, and students' guardians, and the lack of a sense of discipline of students or teachers in reminding students who are not good.